Relationship Between Parental Social Support and Academic Stress of Overseas Students - Sukma, Husnia Hamdyah; Ardi, Zadrian (Jurnal Aplikasi IPTEK Indonesia, 2022)
Self-adjustment is needed by nomadic students, because nomadic students will will adapt and changes to the new environment. Students who are unable to cope will experience stress, therefore adapting campus life is very important. One of the external factors of students academic stress is the lack of social support. This study aims to: (1) describe the social support of parents of nomadic students, (2) describe the academic stress of nomadic students, and (3) to test the relationship of parental social support with the academic stress of nomadic students. This research uses a quantitative approach with a correlational type. The subjects of this study were 137 nomadic students with the Simple Random Sampling technique. The instrument used is a questionnaire using a likert scale. The data were analyzed with descriptive statistical techniques and to test the relationship of social support to academic stress used pearson product moment correlation techniques. The results showed that: (1) the social support of the parents of overseas students was generally in the moderate category, (2) the academic stress of the overseas students was in the moderate category, and (3) there was a relationship between the social support of parents and the overseas students. and academic stress on nomadic students with a correlation coefficient of -0.446 and a significance value of 0.000 and a negative relationship. Based on the research results, it is expected that parents can provide proper social support so that students do not experience academic stress.